Barriers and facilitators to the management of mental health complications after mild traumatic brain injury - Noah D Silverberg; Thalia Otamendi; Amanda Dulai; Ripenjot Rai; Jason Chhina; Anna MacLellan; Pierre-Paul Lizotte (Concussion, 2021)
Background: Clinical practice guidelines for mild traumatic brain injury (mTBI) management call on family physicians to proactively screen and initiate treatment for mental health complications, bu...